Simulation of the primary breakup of a high-viscosity liquid jet by a coaxial annular gas flow. (December 2016) - Müller, T.; Sänger, A.; Habisreuther, P.; Jakobs, T.; Trimis, D.; Kolb, T.; Zarzalis, N.
Highlights: High speed images and LES of breakup of a high-viscous liquid jet by coaxial air. Combination of a compressible LES with the VOF method. CFD code was validated for a broad range of gas velocities. Primary breakup is controlled by a Kelvin–Helmholtz instability. Graphical abstract: Abstract: The conversion of low-grade fossil and biogenic energy resources (petcoke, biomass) to a synthesis gas in a high pressure entrained flow gasification process opens a wide spectrum for high efficient energy conversion processes. The synthesis gas can be used for production of methane (SNG), liquid fuels (BtL, CtL) or as fuel for operation of a gas turbine in a combined cycle power plant (IGCC). The production of a tar free high quality syngas is a challenging objective especially due to the fact that typical liquid or suspension fuels for entrained flow gasifiers feature viscosities up to 1000 mPas. Fuel droplet conversion at typical entrained flow gasification conditions is characterized by heat up, evaporation and subsequent degradation of the vapour phase. To guarantee a high fuel conversion rate in the gasifier an efficient atomization of the fuel is required. Mainly twin-fluid burner nozzles are used for atomization of those typically high viscous fuels. The present study is focused on the assessment of the accuracy of CFD computations for the primary breakup of high-viscosity liquids using an external mixing twin fluid nozzle. In a first step experiments were performed with a Newtonian glycerol-water-mixture featuring a liquid viscosity of 400 mPas. Jet breakup was investigated using a high speed camera as well as PIV and LDA-System for a detailed investigation of the flow field. In a second step the experimental results serve as reference data to assess the accuracy of CFD computations. Compressible large eddy simulations (LES) were performed to capture the morphology of the primary breakup as well as the important flow field characteristics. A Volume of Fluid (VOF) approach was used to track the unsteady evolution and breakup of the liquid jet. Comparison of experimental and numerical results showed good agreement with respect to breakup frequency, velocity fields and morphology.